Instruction set extensions for the advanced encryption standard on a multithreaded software defined radio platform. (9th August 2010) - Jenkins, Christipher; Schulte, Michael; Glossner, John
Software-defined radio (SDR) is an emerging technology that facilitates having multiple wireless communication protocols on one device. Previous work has shown that current wireless communication protocols can run on this class of device while consuming significant processing power. Next generation wireless networks require speeds in excess of 50 Mbps. Some of the fastest software implementations of the advanced encryption standard (AES) only achieve 20 Mbps on our reference platform. In order to have secure software-defined radio, the security processing gap must be addressed. This paper presents instruction set architecture (ISA) extensions for the sandblaster digital signal processor (DSP). The sandblaster DSP is a multithreaded processor for SDR that issues multiple operations each cycle and supports vector operations. Our proposed ISA extensions and hardware designs provide significant performance improvements for AES cryptography and should also work well with other types of embedded processors.